Beta‐Lactam Antibiotics Promote Extracellular Vesicle Production of Staphylococcus aureus Through ROS‐Mediated Lipid Metabolic Reprogramming - Xiaonan Huang; Zhen Hu; Weilong Shang; Juan Chen; Qiwen Hu; Yumin Zhou; Ruolan Ding; Jing Yin; Mengyang Li; He Liu; Jianxiong Dou; Huagang Peng; et al. (Journal of Extracellular Vesicles)
ABSTRACT Bacterial extracellular vesicles (EVs) are natural reservoirs of biological active substances. They exhibit promising application in developing bioproducts such as vaccine, drug‐delivery system and anticancer agent. However, the low yield of naturally secreted EVs during bacterial growth is a bottleneck factor that restricts EV applications. In this study, we showed that sub‐minimum inhibitory concentration (MIC) of β‐lactams boosted EV production in various Staphylococcus aureus strains. The expression of penicillin‐binding protein (PBP) genes increased after β‐lactam treatment, and the inactivation of alternative PBPs promoted EV secretion of S. aureus. We also demonstrated that sub‐MIC β‐lactams promoted EV production via a reactive oxygen species (ROS)‐dependent pathway. Deletion of redundant pbp genes enhanced oxacillin (OXA)‐stimulated ROS levels. Transcriptomic and lipidomic analyses revealed that OXA‐induced ROS triggered lipid metabolic reprogramming in S. aureus. Particularly, ROS promoted lipid peroxidation (LPO) and increased the biosynthesis of phosphatidic acid (PA) and lipoteichoic acid (LTA) that contributed to EV generation. Furthermore, OXA treatment altered the diversity of EV‐loaded proteins. OXA‐treated ∆agr/OXAEVs induced stronger Dengue EDIII‐specific antibodies in BALB/c mice than did ∆agrEVs. Overall, this study provided mechanic insights into β‐lactam‐promoted EV production in S. aureus, and highlighted the potential strategies to prepare EVs for various applications.